Pain management in outpatient hysteroscopy - Cristina del Valle; Juan Antonio Solano; Antonio Rodríguez; Mónica Alonso (Wolters Kluwer Medknow Publications, 2016)
We have performed a review of literature to find evidence on the effectiveness of the different methods used to decrease pain perception during office hysteroscopy and identify risk factors of a painful hysteroscopy. Our methods include a review of literature following the Meta-analysis of Observational Studies in Epidemiology (MOOSE) Guidelines for Systematic Reviews of Observational Studies; a literature search of MEDLINE, Embase, PubMed, and the Cochrane Library of Systematic Reviews; and reference search in selected papers, looking for meta-analysis and randomized controlled trials that assess pain management in office hysteroscopy and studies that identify risk factors for painful hysteroscopy. Review for appropriateness and allocation according to type of analgesic method was performed, together with evaluation for risk factors and evidence of pain reduction effects of pharmacological and nonpharmacological analgesic methods. Nonpharmacological methods, such as vaginoscopy or minihysteroscopes, are advisable to avoid producing pain. The only pharmacological method that has demonstrated its effectiveness in several meta-analysis and reviews is paracervical block, reducing pain during and 30 minutes after hysteroscopy. Nonsteroidal anti-inflammatory drugs (NSAIDs) seem to be useful in the postoperative period. Evidence is not clear about combination of techniques or misoprostol. Although this review is limited because of heterogeneity of the studies included, it gives a wide overview of the different methods that are available to alleviate pain in office hysteroscopy. Paracervical infiltration is the only anesthetic procedure that has proven effective for pain reduction. Other methods such as using NSAIDs, topical anesthetics, misoprostol, or nitrous oxide have to be better studied to reach conclusions on their effectiveness.